Bargaining unexplained - Dan Usher (Queen's University, Department of Economics, 2009)
We know that people strike bargains and that civilized life could not proceed otherwise. We do not know how bargains are struck. We have no explanation of bargaining, comparable to the general equilibrium in the economy, accounting for essential features of bargaining as we know it with reference to universal self-interested behaviour subject only to economy-wide rules. This claim is supported here in a survey of the principal models of bargaining: as a reflection of a shared sense of fairness, as an imposed sequence of offers, as a source of transaction cost and as a species of conflict. Also discussed is the dual role of bargaining in politics as a necessary complement to voting and as an impediment to the exploitation of minority groups.
Keywords: C07; 330; Bargaining; Comprimise; Fairness; Self-interest; Transaction cost; Conflict; Verhandlungstheorie; Eigeninteresse; Konflikt; Gerechtigkeit; Transaktionskosten; Minderheitenpolitik